The local impact of the Presidents Cup 2003 What lessons for sports tourism and development in South Africa? - Kies, Carolynne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Political Science. International Studies))--University of Stellenbosch, 2005.